2011
DOI: 10.14527/c1s4m7
|View full text |Cite
|
Sign up to set email alerts
|

A primary investigation of professional help-seeking attitudes, self-concealment and gender roles of university students

Abstract: The aim of this study is to investigate the professional help-seeking attitudes of university students from their gender, gender roles, the perspective of socioeconomic level and self concealment. Professional Help-Seeking Attitudes Scale-Short Form, Self-Concealment Scale, Bem Gender Role Inventory, and personal information form have been used as data gathering tools. Data were analyzed by using descriptive statistics, t-test and one way anova. The results of the study show that professional help-seeking atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 42 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…When the studies are examined, gender is effective in the attitude of seeking psychological help (Cheng et al 2018). Studies have shown that women exhibit more positive attitudes than men (Atik and Yalçın 2011, Özbay et al 2011, Heath et al 2016, Rayan and Jaradat 2016, Li et al 2018, Çebi and Demir 2020, Topkaya 2021.…”
Section: Attitudes Towards Seeking Psychological Helpmentioning
confidence: 99%
“…When the studies are examined, gender is effective in the attitude of seeking psychological help (Cheng et al 2018). Studies have shown that women exhibit more positive attitudes than men (Atik and Yalçın 2011, Özbay et al 2011, Heath et al 2016, Rayan and Jaradat 2016, Li et al 2018, Çebi and Demir 2020, Topkaya 2021.…”
Section: Attitudes Towards Seeking Psychological Helpmentioning
confidence: 99%
“…Dinar (2022) emphasized how important it is to consider the financial burden of psychotherapy costs while deciding whether to start, continue, or end therapy. Regarding attitudes toward psychological help-seeking, studies suggest that women exhibit more favorable attitudes compared to men (Türküm 2005, Özbay Terzi et al 2011…”
Section: Therapeutic Services In Turkeymentioning
confidence: 99%
“…The literature on psychological help-seeking behavior includes gender (Koydemir Özden 2010, Güç 2014, Topkaya 2014b, Çamaş 2017, socioeconomic level (Erkan et al 2012), gender roles (Türküm 2005, Terzi et al 2011, Kalkan and Odacı 2016, Worthley et al 2017, Gök 2019) past experience of receiving help, (Vogel and Wester 2003, Vogel et al 2005, Atik and Yalçın 2011 expected benefit and risk from the service, (Vogel et al 2008, Topkaya 2011) perceived social support, (Topkaya and Büyükgöze 2015, Yalçın 2016, Çebi and Demir 2020 volunteering to receive psychological help (Erkan et al 2012) intention to receive psychological help, (Vogel et al 2005, Vogel et al 2007, Topkaya 2014a, Topkaya and Büyükgöze-Kavas 2015 self-disclosure (Komiya et al 2000, Vogel andWester 2003) self-esteem (Gürsoy and Gizir 2018), social stigmatization (Vogel et al 2005, Topkaya, 2014b, Heath et al 2018 self-stigmatization (Vogel 2006, Güç 2014) personality traits (Atik and Yalçın 2011) and self-compassion (Heath et al 2018).…”
Section: Gender Ratios In Seeking Psychological Helpmentioning
confidence: 99%
“…When the past research results presented above are considered as a whole, international studies specifically focused on male samples and addressed men's help-seeking behaviors together with gender roles (Vogel and Heath 2016). On the other hand, when Turkish literature on this subject is reviewed, studies examined gender as a categorical variable and explored mean differences or the relationship between gender and psychological help-seeking attitudes (Kalkan and Odacı 2005, Türküm 2005, Atik and Yalçın 2011, Özbay et al 2011, Erkan et al 2012, Topkaya and Meydan 2013, Güç 2014, Topkaya 2014a, 2014b, Gürsoy and Gizir 2018, Çebi and Demir 2020, Topkaya 2021.…”
Section: Gender Ratios In Seeking Psychological Helpmentioning
confidence: 99%